2008
DOI: 10.1111/j.1365-294x.2008.03919.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐species hybridization among Neotropical cats of the genusLeopardus, and evidence for an introgressive hybrid zone betweenL. geoffroyiandL. tigrinusin southern Brazil

Abstract: Natural hybrid zones between distinct species have been reported for many taxa, but so far, few examples involve carnivores or Neotropical mammals in general. In this study, we employed mitochondrial DNA (mtDNA) sequences and nine microsatellite loci to identify and characterize a hybrid zone between two Neotropical felids, Leopardus geoffroyi and L. tigrinus, both of which are well-established species having diverged from each other c. 1 million years ago. These two felids are mostly allopatric throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 63 publications
3
90
0
6
Order By: Relevance
“…S8) showed large mitochondrial and nuclear divergence (11.0%-15.3% and 0.5%-0.6%, respectively) from Brazilian tigrinas, as well as from the Geoffroy's cat and kodkod (L. guigna). Tigrinas have not been extensively sampled for genetic variation across the northern part of their range; however, our data support previous observations based solely on mtDNA (Johnson et al 1999;Trigo et al 2008) of the potential existence of an additional, presently unrecognized Central American cat species.…”
Section: Felid Diversification and Evidence For Hybridizationsupporting
confidence: 80%
See 3 more Smart Citations
“…S8) showed large mitochondrial and nuclear divergence (11.0%-15.3% and 0.5%-0.6%, respectively) from Brazilian tigrinas, as well as from the Geoffroy's cat and kodkod (L. guigna). Tigrinas have not been extensively sampled for genetic variation across the northern part of their range; however, our data support previous observations based solely on mtDNA (Johnson et al 1999;Trigo et al 2008) of the potential existence of an additional, presently unrecognized Central American cat species.…”
Section: Felid Diversification and Evidence For Hybridizationsupporting
confidence: 80%
“…Recent genetic evidence suggests complex patterns of admixture in felids of the Neotropical genus Leopardus, including the presence of cryptic species (Trigo et al 2008(Trigo et al , 2013. These observations are matched by the prevalence of felid hybridization in captivity (Gray 1972), which has generated numerous hybrids of both large cats and medium to small cats.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 68%
See 2 more Smart Citations
“…This molecular study also showed no evidence of gene flow between the southern population (L. guttulus) and the northeastern Brazilian population (named in the article as L. tigrinus), which have contiguous geographical distributions. Although these two closely related species do not interbreed, there are reports of hybridization between L. guttulus and L. geoffroyi in the state of Rio Grande do Sul, southern Brazil Trigo et al, 2008Trigo et al, , 2013Trigo et al, , 2014, and with Leopardus braccatus (named in the article as Leopardus colocolo) in Central Brazil (Trigo et al, 2008(Trigo et al, , 2013(Trigo et al, , 2014. In a recent molecular study, Li et al (2016) reported that the tigrinas from Northeastern Brazil had pampas cat mtDNA within a tigrina nDNA background, as well as nuclear signatures indicating an ancient hybridization with L. geoffroyi.…”
Section: Introductionmentioning
confidence: 99%